Ensuring Healthy Seed Through Innovative Techniques of Seed Potato Production - Sadawarti, Murlidhar; Singh, S. P.; Singh, R. K.; Buckseth, Tanuja; Katare, Subhash; Kumar, Manoj; Khambalkar, P. A.; Singh, Y. P.; Sharma, S. K.; Gupta, S. K.; et al. (Chronicle of Bioresource Management, 2021)
Potato seed is accounting for 40-50% of the total cost of potato cultivation. The availability of quality seed of improved potato varieties in adequate quantities is the major constraint in enhancing productivity of the crop. Presently basic seed of potato in India is produced through conventional system i.e., through clonal selection, tuber indexing and stage-wise field multiplication of healthy indexed tubers in subsequent four generations. However, in hi-tech system, potato is seed produced through microplant, micro tubers, aeroponic mini tuber and apical rooted cutting which inturn will be multiplied under seed plot techniques. This technique enables large scale multiplication of healthy plants round the year which is not possible under conventional system and reduces the field exposure and thereby minimizing the accumulation of viruses in the seed stocks. In this article, we gave an overview of novel seed production methods in potato.